Experiences of the nursing professional when caring for the patient in the process of agony in a local hospital in Chiclayo - Venegas Gutiérres, Cristian Enrique (2022)
Objective: To describe the nursing professional's experiences with patients in the process of agony, in the Internal Medicine services of men and women at the Las Mercedes Teaching Hospital. Method: Qualitative study, with a case study approach. Eight nurses participated with informed consent, the sample was non-pyrobalistic and was determined by the saturation and redundancy technique. In the data collection, the semi-structured interview validated by expert judgment was used and in the data process, content analysis was used, the atopic principles and scientific rigor supported the investigation. Main results: Three categories emerged; emotions and shocking experiences during the patient's agony stage; patient care in the agony process and formative recommendations for patient coping in the agony process. Overall conclusion: When nursing professionals provide care to agony patients, they do so in the physical dimension, by satisfying basic needs, offering them psychological and spiritual support according to the religion they profess and praying for them, involving the family as they provide them with education so that they stop seeing death as the worst thing that can happen to them; but rather as the beginning of a new stage.